An Analysis of the Legal History and Economic Impact of Federal Minimum Wage Policy in the United States - Villa, John (Bellarmine Law Society Review, 2025)
This paper examines the evolution of the political and economic dynamics behind federal minimum wage policy by describing its history in detail. From judicial decisions about the role of the federal government in wage regulation, to the expansive policies of the New Deal Era, to the Reagan era's rejection of such a vast role of the federal government, the history of federal minimum wage policy is far from linear. Evolving political dynamics, jurisprudence, and economic theories have prevented a clear opinion on the legitimacy of a federal minimum wage from emerging. Today, advocates for free market purity dominate the federal government's approach to wage regulation, with meager increases - or no increases at all - becoming commonplace for Congress. As the paper demonstrates, the wage of $7.25 an hour is no longer able to ensure a decent quality of life for Americans. Its proposal to slowly raise the wage to $17 is complemented by two tax credits aimed at minimizing the increased labor costs that small businesses will face, while also recognizing the need for increased buying and saving power for low-wage Americans.